How Criminology and Victimology Answer the Problem of Rape Victim Protection? - Rahman, Malik Akbar Mulki; Firdaus, Nafiis Daffa; Wijatmoko, Mario Sulistiyo (Law Research Review Quarterly, 2023)
This paper explores the intersection of criminology and victimology in addressing the multifaceted challenge of protecting rape victims. Rape, as a heinous crime, not only inflicts physical harm but also leaves enduring psychological scars on survivors. Drawing on criminological perspectives, the paper delves into the root causes of sexual violence, examining societal and systemic factors that contribute to its prevalence. Understanding the underlying dynamics is crucial for formulating effective preventive measures. In parallel, victimology provides a lens to analyze the experiences of rape survivors, emphasizing the need for a comprehensive support system. Examining the role of law enforcement, legal frameworks, and community support, this paper evaluates the existing mechanisms for victim protection and their efficacy. Special attention is given to the challenges faced by rape victims in reporting incidents, seeking justice, and reintegrating into society. The paper further explores emerging trends and innovative approaches within criminology and victimology that aim to enhance rape victim protection. This includes the integration of technology, victim-centered legal reforms, and community-based initiatives. By synthesizing insights from these disciplines, the paper proposes a holistic framework for addressing the complex issues surrounding rape victim protection. Ultimately, the synthesis of criminological and victimological perspectives provides a comprehensive understanding of the challenges faced by rape victims and offers valuable insights for policymakers, law enforcement, and support organizations. The proposed framework encourages a multidisciplinary approach to create a more robust and empathetic system that prioritizes the protection and well-being of those affected by sexual violence.